032 Rapid Guidelines: A Systematic Review. (15th August 2013) - Falavigna, M; Ikobaltzeta, I; Sakhia, F; Zhang, Y; Santesso, N; Norris, S; Schünemann, H
Abstract : Background: Guidelines often take two or more years to be developed. This timeframe is not practical for providing guidance in situations when rapid advice is needed. Objectives: To describe current practices about the development of rapid guidelines and to provide advice about adequate methodology. Methods: We performed a systematic review, including grey literature, to identify (1) rapid guidelines, defined as guidelines produced in a shortened time frame, and (2) methodological manuals addressing its development. Results: We only documents by WHO and NICE that described methods and actual guidelines. The WHO handbook describes "rapid advice guidelines"; guidelines produced in response to a public health emergency in which WHO is required to provide rapid global leadership and guidance. This advice should be produced within 1 to 3 months and be evidence-informed, however, it may not be supported by full reviews of the evidence. We identified six WHO rapid guidelines and one methodological guidance paper based on a WHO guideline. NICE produces "short clinical guidelines"; guidelines that address only part of a care pathway, allowing rapid (11–13-month) development of guidance on aspects of care for which the NHS requires urgent advice. We identified 18 NICE short clinical guidelines. Discussion: Literature is lacking about rapid guidelines and the intended role appears to differ. Despite its relevance, there are few rapid guidelines published and clarity about the terminology is needed. Implications for Guideline Developers: We will provide a framework for those developing rapid guidelines, including practical advice and clarification about the terminology used.